2004
DOI: 10.1097/01.jnr.0000387506.06502.90
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Intelligent, Triage-Based, Mass-Gathering Emergency Medical Service PDA Support Systems

Abstract: The support systems for the Emergency Medical Services (EMS) at mass gatherings, such as the local marathon or large international baseball games, are underdeveloped. The purposes of this study were to extend well-developed, triage-based, EMS Personal Digital Assistant (PDA) support systems to cover pre-hospital emergency medical services and onsite evaluation forms for the mass gatherings, and to evaluate users' perceived ease of use and usefulness of the systems in terms of Davis' Technology Acceptance Model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…While personal experience or anecdotal information is heavily relied upon, the conclusions of many of the studies have suggested that PDAs and pocket PCs have a beneficial effect on clinical practice (Sauser 2002, Bosma et al. 2003, McCord 2003, Chang et al. 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While personal experience or anecdotal information is heavily relied upon, the conclusions of many of the studies have suggested that PDAs and pocket PCs have a beneficial effect on clinical practice (Sauser 2002, Bosma et al. 2003, McCord 2003, Chang et al. 2004).…”
Section: Introductionmentioning
confidence: 99%
“…2003). Chang et al. (2004) studied the effectiveness of a PDA‐based emergency medical triage support system at mass gatherings.…”
Section: Introductionmentioning
confidence: 99%
“…In Tech Specs project, a new type of networks for disaster areas called WIISARD [13] is developed. Furthermore, a study which display information collected through wireless sensor network to the personal digital assistance (PDA) has been conducted [14], [15], [16]. Medical staff can get information quickly that they want now by carrying information terminal displayed injured people information.…”
Section: A Medical Support Using Electronic Equipmentmentioning
confidence: 99%
“…Simulations are an increasingly popular means of offering training to these key groups [34,35]. New technologies are also a popular way to offer training and support for preparedness [36,37]. There is still debate as to the best means to evaluate the effectiveness of simulations and other training exercises [38,39].…”
Section: Preparednessmentioning
confidence: 99%